A Case of Transient Cortical Blindness in Posterior Reversible Encephalopathy Syndrome in the Late Postpartum Period (Global Journal of Medical Research, 2020)
Investigations: Laboratory findings were -Hb-11.6gm%, TLC-11500cmm, Platelet count-2.75 lakhs/cmm; No proteinuria; PT, APTT, INR -within normal limits. LFT,RFT-